(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2021)
The purpose of this study was to determine the presence of digestive tract nematodes in the Bligon goat in the Tahunan village of Grobogan . There were 35 Bligon goats from Langgeng Makmur Farmer Group used for their feces to be sampled. Feed were given peanut straw and lamtoro. Qualitative examination was carried out using the Native method. The variables observed were the level of worm infection in goats and identification of worm eggs based on literacy The results shows that It was detected that as much as 60% of the bligo goats population in the Tahunan village of Grobogan have nematode worm eggs. Worms detected were Strongyloides sp. 34% while Trichuris sp. were 26% of 35 samples of Bligon goat feces. It was concluded that most of the Bligon goats are 60% detected by nematodes. Key words: Bligon goat, nematode worms, Tahunan Grobogan Village